LLMs as an Abstraction Layer in Computer Organization: Implementation and Limitations - Hoffmann, Hugo; Spesse, Carollini Maria P. (Anais do Seminário Integrado de Software e Hardware (SEMISH), 2026)
This paper proposes that Large Language Models (LLMs) can be viewed as a new abstraction layer capable of addressing an intrinsic limitation of traditional presentations of computer organization: the absence of a mechanism that directly connects natural language to the electronic operations performed by hardware. We argue that, although high-level programming languages provide significant abstractions over processor architecture, they do not fully achieve the theoretical objective of translating human commands into electrical signals. We demonstrate how this gap can be addressed through the Model Context Protocol (MCP), which facilitates mediation between commands expressed in natural language and the operating system. Finally, we discuss the problems and vulnerabilities introduced by this new layer, as well as mitigation strategies associated with its use.